2020
DOI: 10.1002/jbt.22639
|View full text |Cite
|
Sign up to set email alerts
|

Citronellal ameliorates doxorubicin‐induced hepatotoxicity via antioxidative stress, antiapoptosis, and proangiogenesis in rats

Abstract: Doxorubicin (DOX) is a very effective broad‐spectrum anticancer drug, yet its clinical application is badly restricted due to its serious side effects. Citronellal (CT), a specialized metabolite of plants found in Cymbopogon spp., is proved to exhibit many beneficial properties. In the current study, we intended to investigate the effect of CT on DOX‐induced hepatotoxicity in rats. Rats were treated with CT (200 mg/kg b.w./day orally), and given DOX (2.5 mg/kg b.w./week, intraperitoneally) to induce hepatotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…These data demonstrated that DOX increased hepatic function serum ratio, including AST, ALT, and ALP levels. These effects were reported in an animal model involving DOX-induced hepatotoxic [ 46 ].…”
Section: Discussionmentioning
confidence: 91%
“…These data demonstrated that DOX increased hepatic function serum ratio, including AST, ALT, and ALP levels. These effects were reported in an animal model involving DOX-induced hepatotoxic [ 46 ].…”
Section: Discussionmentioning
confidence: 91%
“…Then, the quantity of ROS presentation and antioxidant ratio could lead to more tissue destruction. It is confirmed that the DOX-induced ROS and its metabolites begin necrosis and apoptosis using caspase three and receptors in the liver (13). Detoxification of many drugs and toxins is ongoing by the liver.…”
Section: Introductionmentioning
confidence: 80%
“…The doxorubicin is also reactive against cytoplasmic aconitase. The reactivity of doxorubicinol causes an increase in free iron content [3,25].…”
Section: A B Cmentioning
confidence: 99%